2011
DOI: 10.1111/j.1753-9137.2011.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Women (Not) Watching Women: Leisure Time, Television, and Implications for Televised Coverage of Women's Sports

Abstract: This research explores the factors in choices women make about watching sports.The assumption about coverage of women's sports in post-Title IX decades has been that girls who have played will turn into women who watch, encouraging media producers to provide more women's sports programming. Yet that audience has not materialized, and women's sports have languished on the periphery of the sports media landscape. Using focus-group discussions with heterosexual, married women, we argue that sports media consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 53 publications
1
39
0
2
Order By: Relevance
“…Masculinities, expressed through masculine discourses, are identified as socially constructed, privileged ways of thinking that dominate society and are often associated with men but may also be associated with women (Whiteside & Hardin, 2011). In contrast, femininities, expressed through feminine discourses, are socially-constructed ways of thinking, featuring behaviours that are socially understood to be subordinate and are often, but not exclusively, expressed by women (Tsai, 2010b).…”
Section: Women's Leisure Opportunities and Provisionsmentioning
confidence: 99%
“…Masculinities, expressed through masculine discourses, are identified as socially constructed, privileged ways of thinking that dominate society and are often associated with men but may also be associated with women (Whiteside & Hardin, 2011). In contrast, femininities, expressed through feminine discourses, are socially-constructed ways of thinking, featuring behaviours that are socially understood to be subordinate and are often, but not exclusively, expressed by women (Tsai, 2010b).…”
Section: Women's Leisure Opportunities and Provisionsmentioning
confidence: 99%
“…Indeed, one of the greatest hardships for Page373 women's sports to overcome is the small amount of media coverage they get. Scholars have studied the issue for more than three decades in traditional media and found that women's sports are greatly underrepresented compared to men's sports, and that female athletes are often framed as women rather than athletes, while the opposite is true for male athletes -in both print (Boutilier & SanGiovanni, 1983;Lumpkin & Williams, 1991;Christopherson, Janning, & McConnell, 2002;Hilliard, 1984;Eastman & Billings, 2000;Allen & Frisby, 2017) and on television (Adams & Tuggle, 2004;Cooky et al, 2015;Musto et al, 2017;Turner, 2014;Whiteside & Hardin, 2011). The one exception comes every four years during the summer Olympics when female athletes receive as much or sometimes even more media coverage than male athletes do (Billings & Young, 2015;Coche& Tuggle, 2016).…”
Section: Gender Sports and Media Coveragementioning
confidence: 99%
“…The 2013 NCAA Division I Men's Basketball Tournament received its highest television rating since 2005 (Bibel, 2013). Women's sports have also seen an increase in popularity as several college sports specific television networks such as ESPNU, Fox College Sports, and the Big Ten Network frequently broadcast softball, volleyball, and women's basketball (Whiteside & Hardin, 2011).…”
mentioning
confidence: 99%